Long-term cancer risk associated with lung nodules observed on low-dose screening CT scans. (January 2020) - Pinsky, Paul; Gierada, David S.
Highlights: The presence of nodules on low-dose CT screening was associated with increased risk of lung cancer up to 12 years later. Lung cancers diagnosed even more than 4 years after nodule detection tended to occur in the same lung lobe as the nodule. Long-term lung cancer risk differed based on the size and attenuation of nodules. Abstract: Objective: Non-calcified nodules (NCNs) associated with false positive low-dose CT (LDCT) lung cancer screens have been attributed to various causes. Some, however, may represent lung cancer precursors. An association of NCNs with long-term lung cancer risk would provide indirect evidence of some NCNs being cancer precursors. Methods: LDCT arm participants in the National Lung Screening Trial (NLST) received LDCT screens at baseline and years 1-2. The relationship between NCNs found on LDCT screens and subsequent lung cancer diagnosis over different time periods was examined at the person and lobe level. For the latter, a lobe had a cancer outcome only if the cancer was located in the lobe. Separate analyses were performed on baseline and post-baseline LDCT findings; for the latter, those with baseline NCNs were excluded and only new (non-pre-existing) NCNs examined. Raw and adjusted rate-ratios (RRs) were computed for presence of NCNs and subsequent lung cancer risk; adjusted RRs controlled for demographic and smoking factors. Results: 26, 309 participants received the baseline LDCT screen. Over median 11.3 years follow-up, 1675 lung cancers were diagnosed. Adjusted RRs for time periods 0–4, 4–8 and 8−12 years following the baseline screen were 5.1 (95 % CI:4.4–5.9), 1.5 (95 % CI:1.3–1.9) and 1.5 (95 % CI:1.2-1.8) at the person-level and 14.7 (95 % CI:12.6–17.2), 2.6 (95 % CI: 2.0–3.4) and 2.2 (95 % CI:1.6–2.9) at the lobe-level. 18, 585 participants were included in the post-baseline analysis. Adjusted RRs for periods 0–4, 4–8 and 8−11 years were 5.6 (95 % CI: 4.5–7.0), 1.9 (95 % CI: 1.3–2.7) and 1.6 (95 % CI: 0.9–2.9) at the person-level and 19.6 (95 % CI:14.9–25.3), 2.5 (95 % CI:1.3–4.7) and 3.3 (95 % CI:1.4–7.6) at the lobe-level. Raw RRs were similar. Conclusion: NCNs are associated with excess long-term lung cancer risk, suggesting that some may be lung cancer precursors.